Development of Learning Media in Nursing Information Systems Course: Pengembangan Media Pembelajaran pada Matakuliah Sistem Informasi Keperawatan - Mona Yolanda; Tri Monarita Johan; Dini Qurrata Ayuni (Perkumpulan Doktor Indonesia Maju (PDIM), 2021)
The purpose of this research is to develop interactive multimedia-based learning media in the Nursing Information System course for STIKes Nan Tongga Nursing S1 students. The method used in this development is the Research and Development (R&D) method. Research and development methods are methods used to produce certain products, and test the effectiveness of these products. Research and development itself is carried out based on an industry-based development model, the findings of which are used to design products and procedures, which are then systematically field tested, evaluated, refined to meet certain criteria of effectiveness, quality, and standards. The development of interactive multimedia-based teaching materials produces products in the form of learning media using the Macromedia Flash Professional 8 program which is accompanied by a Borg and Gall development design. Interactive multimedia-based learning media in the Nursing Information System course is proven to be able to increase understanding of concepts in Level II students. This can be seen from the results of students' understanding of the average pre-test of the control group 62.31 and the experimental group 69.81.